Analysis of Dependent Variables Following Marshal- Olkin Bivariate Distributions in the Presence of Progressive Type II Censoring - Hiba Muhammed (Statistics, Optimization & Information Computing, 2023)
In this paper, the likelihood function under progressive Type II censoring is generalized for Marshal-Olkin bivariate class of distributions and applied it on the bivariate Dagum distribution. Maximum likelihood estimation is considered for the model unknown parameters. Asymptotic and bootstrap confidence intervals for the unknown parameters are evaluated under progressive Type II censoring. Bayesian estimation is also considered in both complete and progressive Type II censored samples; moreover, the Bayes estimators are obtained explicitly with respect to square error loss function in both cases.